y=-(x+1)(x-3)

Simple and best practice solution for y=-(x+1)(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for y=-(x+1)(x-3) equation:


Simplifying
y = -1(x + 1)(x + -3)

Reorder the terms:
y = -1(1 + x)(x + -3)

Reorder the terms:
y = -1(1 + x)(-3 + x)

Multiply (1 + x) * (-3 + x)
y = -1(1(-3 + x) + x(-3 + x))
y = -1((-3 * 1 + x * 1) + x(-3 + x))
y = -1((-3 + 1x) + x(-3 + x))
y = -1(-3 + 1x + (-3 * x + x * x))
y = -1(-3 + 1x + (-3x + x2))

Combine like terms: 1x + -3x = -2x
y = -1(-3 + -2x + x2)
y = (-3 * -1 + -2x * -1 + x2 * -1)
y = (3 + 2x + -1x2)

Solving
y = 3 + 2x + -1x2

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Simplifying
y = 3 + 2x + -1x2

See similar equations:

| y=(x+2)(x-4) | | H=21+30t-5t^2 | | 2x-7=8-3d | | y=.21(20)+17.5 | | y=(x-2)(x+2) | | graphy=(x-2)(x+2) | | 315=21y | | 2(x-3)-1=6 | | 8y-6+90=180 | | 2l+25.6=768 | | 4(x+3)+7(x+2)=37 | | 51/2m+3 | | y=(x+8)(x+12) | | 2l-30=768 | | y=x^2-3bx+1 | | y=3/4(x+8)(x+12) | | 30x=768 | | 6y-6+90=180 | | 4y^2-28y=-49 | | 0,5(4x-6)=1,5x | | .7h=-.112 | | x^2-9x=-8 | | 2l+30=768 | | x^2-20x-300=0 | | 3x+6y-24=0 | | 8^5/3 | | x+56=83+64 | | 2l+28=476 | | y=1/2(x-2)(x+11) | | 7y^2+14= | | 21+28=476 | | 4(x+3)+7(x+2)=17 |

Equations solver categories